2018
DOI: 10.1155/2018/9187316
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of lncRNA-HEIH and lncRNA-HULC with HBXIP in Hepatitis B Patients

Abstract: Hepatitis B virus (HBV) infection is a major risk factor for the development of hepatic cirrhosis (HC) and hepatocellular carcinoma (HCC), which are associated with very high morbidity and mortality rates worldwide. Many studies have shown that long noncoding RNAs (lncRNAs) that are highly expressed in HCC (lncRNA-HEIH) and highly upregulated in liver cancer (lncRNA-HULC) have been implicated in the development and progression of hepatitis B-related HC and HCC. In this study, reverse transcription and quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…However, beyond a few studies (Singh et al, 2016; Chowdhury et al, 2017), including one which showed that the lncRNAs EGO (NONHSAT087634) and HOTAIRM1 (NONHSAT119666) are alternatively spliced and that expression of lnc-IL7R is increased during LPS induced sepsis (Chowdhury et al, 2017), not much is known about how altered lncRNA expression is related to pathophysiology of sepsis. HULC (highly upregulated in liver cancer) is a 16 kb lncRNA at chromosomal location 6p24.3 and is has been shown to be overexpressed in patients with liver cancer (Ruan et al, 2018). LncRNA urothelial carcinoma-associated 1 (UCA1) at chromosomal location 19p13.12 was initially identified in human bladder carcinoma but plays widespread role in inflammation and tumorigenesis (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, beyond a few studies (Singh et al, 2016; Chowdhury et al, 2017), including one which showed that the lncRNAs EGO (NONHSAT087634) and HOTAIRM1 (NONHSAT119666) are alternatively spliced and that expression of lnc-IL7R is increased during LPS induced sepsis (Chowdhury et al, 2017), not much is known about how altered lncRNA expression is related to pathophysiology of sepsis. HULC (highly upregulated in liver cancer) is a 16 kb lncRNA at chromosomal location 6p24.3 and is has been shown to be overexpressed in patients with liver cancer (Ruan et al, 2018). LncRNA urothelial carcinoma-associated 1 (UCA1) at chromosomal location 19p13.12 was initially identified in human bladder carcinoma but plays widespread role in inflammation and tumorigenesis (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In HBV infection, it is known that several lncRNAs are involved in the development or progression of HBV‐associated HCC (eg, MALAT1, UCA1, DBH‐AS1, Dreh, LINE1, Ftx, and HOTAIR) or were upregulated in HBV infected patients (eg, lncRNA‐HEIH, lncRNA‐HULC, and HBXIP). To understand lncRNAs which likely affect virus replication in host cells, we focused on growth arrest‐specific transcript 5 (GAS5), a critical regulator in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies, HBXIP was elevated in normal gastric mucosa, as well as in gastric cancer tissue and adjacent, noncancerous tissue ( 30 ). Other studies have also confirmed that HBXIP is highly expressed in both liver cancer and ovarian cancer ( 31 , 32 ). These observations indicate that HBXIP plays an important role in the occurrence, invasion, and metastasis of malignant tumors.…”
Section: Discussionmentioning
confidence: 67%